2008
DOI: 10.1017/s1751731108002474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of progesterone on embryo survival

Abstract: Increased genetic selection over the past 40 years has resulted in a dairy cow with an improved biological efficiency for producing milk but with an associated reduced fertility. Embryo loss is the greatest factor contributing to the failure of a cow to conceive. The extent and timing of embryo loss indicates that 70% to 80% of this loss occurs in the first 2 weeks after artificial insemination (AI). This is the period when a number of critical phases in embryo development occur and where protein accretion, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 63 publications
3
59
1
4
Order By: Relevance
“…This supports the data of practitioners, who report about adequate breeding success in the early post-partum period, if they breed only cows which show a good heat in that usually nonrecommended time (Beetz 2012). But these results are in contrast to other studies, which identified low follicle (Lopez et al 2005;Mussard et al 2007;Leroy et al 2008) or CL quality (Lucy 2001;Wathes et al 2003;Morris and Diskin, 2008;Clemente et al 2009) in the early post-partum period as a reason for increased infertility in dairy herds. It is possible that infectious courses are more important than follicle or CL quality in determining the decrease in fertility in cyclic cows during the post-partum period (Azawi 2008).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…This supports the data of practitioners, who report about adequate breeding success in the early post-partum period, if they breed only cows which show a good heat in that usually nonrecommended time (Beetz 2012). But these results are in contrast to other studies, which identified low follicle (Lopez et al 2005;Mussard et al 2007;Leroy et al 2008) or CL quality (Lucy 2001;Wathes et al 2003;Morris and Diskin, 2008;Clemente et al 2009) in the early post-partum period as a reason for increased infertility in dairy herds. It is possible that infectious courses are more important than follicle or CL quality in determining the decrease in fertility in cyclic cows during the post-partum period (Azawi 2008).…”
Section: Discussioncontrasting
confidence: 95%
“…Additionally, lower progesterone levels in the plasma during dioestrus are described in cows compared to heifers (Sartori et al 2004). Both could be a cause for the reduced fertility in the early postpartum period, which is observed in high-yielding dairy herds (Lopez-Gatius et al 2002;Morris and Diskin 2008;Clemente et al 2009;Walsh et al 2011). In recent years there have been incredible advances in our knowledge regarding the molecular regulation of the ovulation process and regulation of growth or regression of the Cl.…”
mentioning
confidence: 99%
“…A number of studies have reported lower P4 in non-pregnant than pregnant cows, whereas, other studies reported no relationship between post-AI P4 and fertility (Bulman and Lamming, 1978; Larson et al, 1997;Mann and Lamming, 1999;Gumen et al, 2003;Stronge et al, 2005;Lonergan et al, 2007;Morris and Diskin, 2008). More extensive logistic regression modeling demonstrated a relationship in dairy cows between P/AI with circulating P4 on days 5, 6 and 7 after AI or with rate of P4 increase after AI (Stronge et al, 2005).…”
Section: Importance Of High P4 After Aimentioning
confidence: 98%
“…For example, in humans, , 8 out of 10 transferred embryos fail to implant successfully (Bromer and Seli, 2008), most likely because of the inability to identify embryos with the best development potential. In cattle, there has been a significant decline in fertility over the past few decades (Dobson et al, 2007;Leroy et al, 2008) because of low fertilization rates and embryonic loss among other factors (Santos et al, 2004;Morris and Diskin, 2008). In order to identify genes affecting embryonic loss, and hence infertility, an IVF experimental system in cattle has been established in our laboratory and several candidate genes have been reported to be associated with embryo development (Khatib et al, 2009;Huang and Khatib, 2010;Huang et al, 2010a and2010b).…”
Section: Introductionmentioning
confidence: 99%